The Relationship between Corporate Governance and Earnings Management: The Case of Malaysia - Nooraisah Katmon; Noor Hanisah Khabli; Zam Zuriyati Mohamad; Norimah Rambeli @ Ramli; Mohd Norullah Ab. Razak (International Business Education Journal, 2022)
We investigate the relationship between corporate governance mechanisms that are audit committee characteristics, board characteristics and earnings management. We used 150 listed firms in Bursa Malaysia as our sample. We analyse our data using descriptive statistics, correlation and regression. Our study found that the size of the board negatively related to earnings management. This suggest that large board are able to provide effective monitoring mechanism to the firm in combating earnings management. Besides, our result also exhibit that the independence of audit committee is also associated with higher earnings management. We conclude that the role of corporate governance mechanisms are important determinants in reducing earnings management in the firms in Malaysia.